THE IMPACT OF VMI ON PERFORMANCE IN MANUFACTURING COMPANY (Journal of Technology and Operations Management, 2012)
The purpose of this paper is to shed the light on the impact of VMI element that lead to high performance of VMI in Malaysia manufacturing company. The VMI elements consist of inventory location, inventory ownership, demand visibility, replenishment decisions, and inventory control limits. Questionnaire was the main instrument for the study and it was gathered from 101 staff in departments of purchasing, planning, logistics and operation. Data analysis was conducted by employing descriptive analysis (mean and standard deviation), reliability analysis, Pearson correlation analysis and multiple regressions. The findings show that there are relationships exist between inventory location, level of demand visibility, inventory control limits and service performance of VMI, but not for inventory ownership and replenishment decisions. Meanwhile, for cost performance of VMI, only inventory location had significant relationship. Visibility of demand is the main predictor of service performance, followed by inventory control limits. However, only inventory location contributes to cost performance of VMI. It is recommended that future study to determine additional VMI element that are pertinent to firms’ current VMI practices. Logic suggests that further study to include more integration issues, other nature of businesses and research instruments.